Government Buildings, Trinidad - Tucker (Davidson and Todd Ltd., Trinidad, 2010)
Exterior view of the government building, the Red House, seat of Parliament in Trinidad and Tobago. A man is standing near the centre foreground of the picture.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Red House, The